Dust Transport to the Taylor Glacier, Antarctica, During the Last Interglacial. Issue 4 (26th February 2019) - Aarons, S. M.; Aciego, S. M.; McConnell, J. R.; Delmonte, B.; Baccolo, G.
Abstract: Changes in the composition of dust trapped in ice provide evidence of past atmospheric circulation and earth surface conditions. Investigations of dust provenance in Antarctic ice during glacial and interglacial periods indicate that South America is the primary dust source during both climate regimes. Here, we present results from a new ice core dust archive extracted from the Taylor Glacier in coastal East Antarctica during the deglacial transition from Marine Isotope Stage 6 to 5e. Radiogenic strontium and neodymium isotopes indicate that last interglacial dust is young and volcanic, in contrast to the observed preindustrial and Holocene (Marine Isotope Stage 1) dust composition. The dust composition differences from the last interglacial and current interglacial period at the site require a profound difference in atmospheric transport and environmental conditions. We consider several potential causes for enhanced transport of volcanic material to the site, including increased availability of volcanic material and large‐scale atmospheric circulation changes. Plain Language Summary: Fluctuations in the isotopic composition of dust particles transported atmospherically and trapped in East Antarctic ice during glacial and interglacial periods provide glimpses into past earth surface conditions and atmospheric dynamics through time. Here we present new ice core records of dust from the Taylor Glacier (Antarctica), extending back to the transition into the last interglacial period ( 130, 000 years ago). Dust deposited at this site during the last interglacial period has a significantly more volcanic dust composition compared to the current interglacial dust, caused by a pronounced wind direction change and/or increased subaerial exposure of volcanic material. The distinct dust compositions during two separate interglacial periods suggest significant differences in conditions at the dust source areas and atmospheric dynamics to this peripheral Antarctic site. Key Points: Last interglacial dust composition in Taylor Glacier ice is distinct from MIS 1 record Sr and Nd isotope signatures indicate a young volcanic source Geochemical data suggest a change in provenance and atmospheric circulation between MIS 5e and MIS 1